Evaluation report of Early Intervention Program in Situations of Youth-to-Parent Aggression: What happens one year after? - Elgorriaga Astondoa, Edurne; Ibabe, Izaskun; Arnoso, Ainara; Asla, Nagore (Anales de Psicología / Annals of Psychology, 2023)
Introduction: The Early Intervention Program in Situations of Youth-to-Parent Aggression (EI-YPA) is the only program for incipient youth-to-parent aggression. It has a good level of protocolization and is open access. The main objective of this study was to evaluate the effect of the EI-YPA program on adolescents in the medium term, as well as the level of satisfaction and acceptability with respect to the subprogram aimed at adolescents. Methods: Among the participants who successfully completed the program, 22 adolescents (between 12 and 17 years old) and 49 parents participated in the study in Spain. A single-case experimental design was applied, allowing the monitoring of change within adolescents through comparison between phases (pre-, post-intervention, and follow-up at 6 months). Results: Empirical evidence favourable to the program was observed, showing reductions in youth-to-parent aggression, clinical symptoms (depressive symptoms, irrational beliefs, a lack of empathy, and emotional instability), and the perception of family conflict in the medium term after the intervention, alongside improved life satisfaction. Conclusions: This study improves the quality of the evidence of this pioneering program, having a positive impact on adolescents in the medium term and good acceptability by adolescents; it can thus be considered a very promising program for the clinical and family protection context.